Libras e ensino de Filosofia: a experiência do pensar pelas mãos que falam - ALMEIDA, Eline Mesquita (2021)
Through theoretical-methodological research, our work aims to establish a link between Philosophy and Libras in a proposal to develop didactic-pedagogical material for teaching Philosophy through the experience of Libras. Philosophy, once established in the school universe, needs to exercise, in a critical-reflective way, a constant awakening to praxis, and, therefore, have an active and transforming role in the teacher-student relationship. In this sense, an education that establishes links that are truly inclusive and focused on citizenship is necessary. Based on studies in the light of Maurice Merleau-Ponty's thought, we can strengthen these links when we begin to understand how the experience of corporeality provides us with both Philosophy and Libras a direct relationship of the language of a subject-body. In the most diverse studied theorists, and especially the one mentioned here, concepts such as body, expression, language, movement, among others, are observed. Thus, in the first chapter we will make a historical journey of the absence-presence of Philosophy in the Brazilian education system. We will see the philosophical currents and the education system of the deaf, seeking to elucidate what deafness and sign languages are, and we will also share knowledge about deaf epistemology, linking to corporeality present in Libras signs. In the second chapter, we will reflect on themes such as perception, self-body, expression, language and speech. Such themes are of great sustainability to our work, and along this path we use many works, but as main reading, the work Phenomenology of Perception by Merleau-Ponty. With regard to the third chapter, we have the practical part of our research on the teaching of Philosophy through the enunciation of Libras: this is the moment to materialize the experience of thinking through the hands. The research to be carried out has as its locus the CAS - Prof. Maria da Glória Costa Arcangelli Support Teaching Center for People with Deafness and will be developed in stages that follow from philosophical workshops. The workshops will be transcribed to |LIBRAS after being analyzed by the teacher, students and interpreters in order to develop and improve pedagogical teaching material for the teaching of philosophy through the enunciation of LIBRAS.